Perencanaan Desain Tempat Pengolahan Sampah 3R (Reuse, Recycle, Reduce) di Wilayah Gresik Utara - Dinda Apriliya Tri Utami; Firra Rosariawari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The state of population growth, which is increasing every year and is not balanced by adequate waste processing facilities, has resulted in many illegal waste dumps. The direction for developing a waste system is carried out as an effort to reduce the burden of waste processing and extend the life of the landfill. The aim of this research is to plan TPS 3R as an effort to manage waste and can be used as material for consideration in planning the construction of TPS 3R in the future. The emergent sampling method refers to 19-3964-1994. Meanwhile, planning is being carried out based on the 3R TPS Technical Instructions by the Director General of PUPR in 2020. The average waste generation is 0.285 Kg/org/d with a volume of 0.00136 m3/org/d. The composition of the waste is 53.48% inorganic and 46.52% organic. The 3R TPS to be built will require a floor area of 588.19 m2. The capacity of waste to be treated is 20.4 m3/day. The 3R TPS is planned to use an open windrow composting process with the help of a bamboo aerator to process organic waste. Meanwhile, inorganic waste will be managed by sorting and grouping by type, which will then be transferred to a third party.